INITIATION ON ECOSYSTEM APPROACH TO FISHERIES MANAGEMENT (EAFM): CASE STUDY ON TARAKAN FISHERIES - Andhika Prima Prasetyo; Duto Nugroho; Wudianto Wudianto; Hari Eko Irianto; Purwanto Purwanto (Research Center for Fisheries, 2014)
An EAFM from a global perspective is still moving towards on implementation. EAFM is based on conventional fisheries management but broadens the perspective beyond seeing a fishery as simply “fish in the sea, people in boats,” beyond consideration only of commercially important species, and beyond management efforts directed solely at the harvesting process. This research aims to initiate implementing EAFM in Indonesia: case in Tarakan Fisheries, North Kalimantan Province. From the initiate implementation of EAFM, we found that the possibility to improve the performance on arrange fisheries management based on ecosystem approach. EAFM could be used as tools to confirm scientific findings and gathering initial information on fisheries. In the case, fisheries community in Tarakan was put human well-being as important point to determine fisheries management, rather than ecological well-being. To secure the fisheries the possible options would arrange accepted and adaptable policy on controlling fisheries i.e. temporary fishing closure in term of area and season.